Reliability Analysis of the Reconfigurable Integrated Modular Avionics Using the Continuous-Time Markov Chains - Changxiao Zhao; Peng Wang; Fang Yan (International Journal of Aerospace Engineering)
The integrated modular avionics (IMA) has been widely deployed on the new designed aircraft to replace the traditional federated avionics. Hosted in different partitions which are isolated by the virtual boundaries, different functions are able to share the common resources in the IMA system. The IMA system can dynamically reconfigure the common resources to perform the hosted functions when some modules fail, which makes the system more robust. Meanwhile, the reliability of the reconfigurable integrated modular avionics becomes more complicated. In this paper, we firstly model the IMA as a joint (m,k)-failure tolerant system with the consideration of its reconfigurable capability. Secondly, the continuous-time Markov chains are introduced to analyze the reliability of the IMA system. Thirdly, we take the comprehensive display function hosted in the IMA system as an example to show the practical use of the proposed reliability analysis model. Through the parameter sensitivity analysis, different failure rate λ and priority order of different modules are chosen to analyze their impact on system reliability, which can provide guidance to improve the reliability of the IMA system during a dynamic reconstruction process and optimize resource allocation.